Poverty in Indonesia in The Era of Social and Digital Transformation: Analysis From The Perspective of Social Education Science - Dahlia - (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
Poverty remained one of the most complex development challenges in Indonesia. Although national poverty rates had shown a downward trend in recent years, various phenomena such as multidimensional poverty, vulnerable poor groups, educational gaps, digital divides, and intergenerational poverty still posed significant problems affecting community welfare. This research aimed to analyze contemporary poverty phenomena in Indonesia from the perspective of Social Education Science. The study employed a library research method with a qualitative approach through the analysis of various scientific literature, government reports, and publications from international organizations. The findings showed that poverty was not only influenced by economic factors but also by disparities in access to education, low social capital, limited digital literacy, and regional development imbalances. Social education played a crucial role in developing critical awareness, enhancing community capacity, strengthening social capital, and promoting community empowerment. Therefore, the integration of social education into poverty alleviation policies was identified as an important strategy to achieve inclusive and sustainable development